Pengaruh Iklim Organisasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Bank UOB Indonesia Cabang PIK Boulevard - Rintis Eko Widodo; Fransiscus Amonio Halawa; Yohannes Don Bosko (Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial, 2023)
ABSTRACT The purpose of this study was to determine the effect of organizational climate and work motivation, either partially or simultaneously (simultaneously) on employee performance at PT Bank UOB Indonesia PIK Boulevard Branch. The research method used is the survey method. Data analysis method is done by using linear regression analysis. From the results of multiple regression analysis carried out in predicting the effect of organizational climate variables (X1) and work motivation (X2) on employee performance (Y), it is known that the organizational climate regression coefficient is 0.454 and the motivation regression coefficient is 0.301, and the coefficient of determination is 0.641 or 64.1 %. The desired increase in employee performance can be explained or improved through increasing organizational climate variables and employee work motivation together, however, the regression coefficient value is more dominant which affects employee performance at PT. Bank UOB Indonesia Branch PIK Boulevard F count 298,413 < F Table 3,191 and Significance value 2,045> 0.05 Then Ha is accepted or H0 is rejected. The results of the hypothesis test conclude that there is a positive and insignificant effect on organizational climate and work motivation on employee performance Keywords: Organization, Work Motivation, Employee Performance.